Gambaran Kepuasan Pasien yang Menggunakan Jaminan Kesehatan (BPJS) terhadap Mutu Pelayanan Keperawatan di Rumah Sakit Kabupaten Jember - Kurnia Rahmawati; Anisah Ardiana; Dicky Endrian Kurniawan (UPT Percetakan dan Penerbitan Universitas Jember, 2020)
Quality of service is a service that suits your needs, affordable, effective, efficient, and no risk to save on expenses. This study aimed to analyze the description of BPJS patient satisfaction with the quality of nursing service at inpatient ward of hospital in Jember. This was a cross sectional study. The subjects of this study were BPJS patients at inpatient ward at hospital in Jember. There were 120 respondents choosed by purposive sampling. Data were collected using the Patient Satisfaction with Nursing Care Quality Questionnaire (PNSCQQ). This study showed that the patient satisfaction is not optimal. Indicators of general perception of patients in each statement showed that 80 patients (63.5%) said the overall quality of health service received was good. The overall quality of nursing service was also said to be good by 80 patients (63.5%). As many as 90 patients (71.5%) agreed that they wanted to recommend one of the hospital in Jember to family and friends who needed help in terms of health service. This research showed that it is important to improve the quality of nursing service to increase patient satisfaction. Nurses need to improve nursing care. This research can be used as a reference and illustration for hospital management, and nurses are expected to implement and improve quality nursing service in order to achieve better health service so patient satisfaction will be increase.